STUDY OF THE ROLE OF RNA-INTERFERENCE IN THE REGULATION OF DISCRETE FRAGMENTATION OF 18S RRNA IN PLANTS (Experimental biology, 2022)
Under stressful conditions, cells must rapidly reduce the level of total mRNA translation, while maintaining the synthesis of some special proteins that help resist stress. In animals and yeast, the inhibition of protein synthesis is mainly associated with the modification of the translation initiation and elongation factors. In plant cells, many of these regulatory mechanisms are not realized. We hypothesize that plants have an alternative mechanism for suppressing mRNA translation associated with site-specific fragmentation of 18S rRNA molecules within 40S ribosomal subunits. Understanding the molecular mechanisms of plant response to stress is the basis for increasing the efficiency of the breeding process in order to develop stress-resistant varieties of economically important plant species. We found that during a heat shock, discrete RNA molecules accumulate in the cells of various plant species, which are 5'-terminal fragments of 18S rRNA that remain bound in the composition of ribosomal subunits. In this work, the method of nucleic acid hybridization was used to study RNA-interference as a possible mechanism mediating the phenomenon of discrete fragmentation of 18S rRNA in plants in response to heat shock. MicroRNA molecules complementary to the target regions of 18S rRNA, through which its rupture was carried out with the formation of stress-induced 5'-terminal RNA fragments, were not found. The small 5'-terminal fragments of 18S rRNA revealed during the work are proposed to be used as a new type of stress biomarkers in plant cells. The optimized nucleic acid hybridization technique using a DIG-labeled probe complementary to the highly conserved 1-35 5'-end region of plant 18S rRNA can be used to efficiently detect these stress RNA markers.
Keywords: discrete fragmentation of 18S rRNA, heat shock, cytoplasmic RNA, translation of mRNA, 40S ribosomal subunits